Using high-sensitivity cardiac troponin for the exclusion of inducible myocardial ischemia in patients without previously known coronary artery disease. (3rd October 2022) - Schaefer, I; Lopez-Ayala, P; Walter, J; Rumora, K; Amrein, M; Zimmermann, T; Boeddinghaus, J; Koechlin, L; Strebel, I; Nestelberger, T; Wussler, D; Puelacher, C; et al.
Abstract: Background: The rapid and safe exclusion of functionally relevant coronary artery disease (CAD) is a crucial, yet unmet clinical need. High-sensitivity cardiac troponin (hs-cTn) may be an attractive strategy, particularly in patients without previously known CAD. Purpose: To derive and internally validate optimal rule-out cutoffs for an early and safe exclusion of functionally relevant CAD in symptomatic patients without previously known CAD. Methods: In an ongoing single-center, prospective, cohort study, we enrolled consecutive patients without previously known CAD that were referred with symptoms possibly related to functionally relevant CAD. Cardiac troponin concentrations were measured at presentation using two high-sensitivity assays (Elecsys hs-cTnT and Architect hs-cTnI). Presence of functionally relevant CAD was adjudicated by 2 independent cardiologists, blinded to hs-cTn measurements, using MPI-SPECT/CT in all patients, as well as coronary angiography and fractional flow reserve measurements, whenever available. The primary diagnostic outcome was safety for early rule-out of functionally relevant CAD, quantified by sensitivity and the negative predictive value (NPV). The co-primary prognostic outcomes were cumulative incidences of cardiovascular death and all-cause death after 5 years. A NPV ≥90% and sensitivity ≥90% were predefined as acceptable performance criteria. The derived cutoffs were further evaluated in pre-specified subgroups. Internal validity was assessed with a bootstrapping procedure for a realistic estimate in similar future patients. Cumulative incidence curves stratified by the presence of functionally relevant CAD and hs-cTn concentrations below and above the derived cutoffs were constructed. Results: Among 2111 eligible patients, 498 (23.6%) had a final diagnosis of functionally relevant CAD. Median age was 68 years and 938 (44.4%) were female. For ruling out functionally relevant CAD, a hs-cTnT concentration <5 ng/L resulted in a sensitivity of 90.8% (95% CI: 87.9–93.0%) and a NPV of 90.2% (95% CI: 87.1–92.5), triaging 468 (22.2%) patients towards rule-out. Similarly, a hs-cTnI concentration <2 ng/L resulted in a sensitivity of 91.6% (95% CI: 88.8–93.7%) and a NPV of 90.0% (95% CI: 86.8–92.6), triaging 422 (20.0%) patients. Internal validation showed robustness of these findings. The diagnostic performance of the derived cutoffs did not significantly vary across the subgroups. Hs-cTn concentrations above the derived cutoffs were associated with a substantially higher cumulative event rate of cardiovascular death (hs-cTnT: 7.0% vs. 0.8%; hs-cTnI: 6.6% vs. 1.2%) and all-cause death (hs-cTnT: 14.3% vs. 2.4%; hs-cTnI: 13.1% vs. 4.4%) during 5-years follow-up (log rank p<0.001 for all). Conclusion: In symptomatic patients without previously known CAD, very low hs-cTn concentrations may generally allow to safely and effectively exclude functionally relevant CAD. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Science FoundationSwiss Heart Foundation